Persepsi Masyarakat Kota Magelang Terhadap Bahaya Rokok Bagi Kesehatan Anak Dengan Riwayat Orang Tua Perokok - Rejeki Sri Mulyaningsih (Politeknik Karya Husada, 2022)
Smoking has become a common thing that is done by the people of Indonesia. Both from among children and parents. Many people smoke near their family members. Even though the cigarette smoke produced is not only dangerous for himself, but also for those around him. Exposure to cigarette smoke can cause various dangerous diseases, especially for children. A person is said to be a smoker not only those who consume cigarettes directly, people who inhale cigarette smoke can also be said to be smokers. People who consume cigarettes directly are called active smokers, while people who inhale cigarette smoke are called passive smokers. Many people know that active smoking parents will endanger the health of their children, but some of them still do not know that passive smoking parents will also have an adverse impact on children's health. The purpose of this study was to determine the perceptions of the people of Magelang city about the dangers of smoking for the health of children with a history of smoking parents. The research method used is a quantitative method by distributing online questionnaires to people in the city of Magelang. The results showed that out of 50 respondents, 81.8% knew the dangers of smoking for children's health, while the rest were still unsure and disagreed. The conclusion obtained is that the majority of respondents know the dangers of smoking for children's health, especially in children with a history of smoking parents.